Przyczynek do dyskusji na temat powstania 1 Kor na wiosnę - Rakocy, Waldemar (The Biblical Annals, 2017)
The contribution undertakes the problem of the season of the year, when St Paul wrote 1 Cor. Among the authors the opinion prevails that it was in the spring months. The author of the article first analyses the events that happened between 1 Cor and the probable leaving Ephesus by Paul (cf. 16, 8); then − how long they lasted: the sea voyage between Ephesus and Corinth that he had to go on a few times. This leads to the conclusion that the hypothesis of ’spring’ is possible only if the Apostle left Ephesus later than on the feast of Quinquagesima. Besides this the author of the article gives two reasons why 1 Cor must have been written in the autumn of the last but one calendar year of Paul’s stay in Ephesus. The first of them is based on an analysis of the course of collection for the poor in Jerusalem, whose beginning is shown in 1 Cor 16, 1-3. The second reason follows from an analysis of the Apostle’s plans in 16, 8-9, which text is an explanation why the stay in Ephesus was prolonged; under different circumstances he would leave the town sooner.